2007
DOI: 10.1109/tpami.2007.1107
|View full text |Cite
|
Sign up to set email alerts
|

Face Recognition Algorithms Surpass Humans Matching Faces Over Changes in Illumination

Abstract: There has been significant progress in improving the performance of computer-based face recognition algorithms over the last decade. Although algorithms have been tested and compared extensively with each other, there has been remarkably little work comparing the accuracy of computer-based face recognition systems with humans. We compared seven state-of-the-art face recognition algorithms with humans on a facematching task. Humans and algorithms determined whether pairs of face images, taken under different il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(109 citation statements)
references
References 23 publications
2
102
0
5
Order By: Relevance
“…However, the adequacy of this ''pigmentation hypothesis'' has been challenged by data showing that hue negation, which also results in unnatural pigmentation (making the entire face look bluish-green), has little effect on recognition performance (11). It is also unclear whether observers can usefully extract pigmentation information across different illumination conditions (17,18). We propose an alternative account of negation-induced impairment.…”
mentioning
confidence: 87%
“…However, the adequacy of this ''pigmentation hypothesis'' has been challenged by data showing that hue negation, which also results in unnatural pigmentation (making the entire face look bluish-green), has little effect on recognition performance (11). It is also unclear whether observers can usefully extract pigmentation information across different illumination conditions (17,18). We propose an alternative account of negation-induced impairment.…”
mentioning
confidence: 87%
“…Even though it was recently demonstrated that machines have started to become more efficient than humans in face recognition in unconstrained conditions [207,208], humans still largely surpass machines in face detection [209]. Nevertheless, it is exciting to see face detection techniques be increasingly used in real-world applications and products.…”
Section: Discussion Future Work and Conclusionmentioning
confidence: 99%
“…Former studies have shown that, when a large number of representative training images are available, computer algorithms are able to recognize even better than humans [6], [7], [25], [27], [33]. These algorithms, before recognizing, represent the face in the feature space, and perhaps because they are able to extract information from training images about the changes caused by different conditions they outperform humans in recognition [25].…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms, before recognizing, represent the face in the feature space, and perhaps because they are able to extract information from training images about the changes caused by different conditions they outperform humans in recognition [25].…”
Section: Introductionmentioning
confidence: 99%